(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The introduction of Information and Communication Technology has revitalized the financial services sector, particularly in the banking sector. With promising fame and competition, most of the banks have accepted the value of electronic banking concept and they are adapting themselves with the innovative technologies. Electronic banking has made the receipts and payments operations of the banks electronically. Electronic banking is playing a significant role in providing classy services to the customers. It facilitates to increase the satisfactory level of the customers, reduces cost, better productivity and a variety of banking operations. The authors have endeavored to illustrate the scope of innovation and the idea shifts taking place in Real Time Gross Settlement, Mobile banking, National Electronic Fund Transfer, Electronic Clearing Service have made a significant move in payment systems through electronic mode.